Using a Tablet Device to Compensate for Underestimation of Cognitive Function due to Impaired Dominant Hand Function in Stroke Patients. Issue 5 (4th May 2017) - Kim, Jungyoon; Kim, Bo Ra; Kang, Ilhyang; Kye, Myung-Eun; Kim, Ju Han; Kim, Jieun E.; Yoon, Sujung; Lyoo, In Kyoon; Lim, Soo Mee
ABSTRACT: This study aimed to investigate whether a touch-screen tablet device can be used to avoid underestimation of cognitive function due to hand disability in patients with stroke. Thirty patients with stroke and hemiplegia were divided according to whether the paretic side corresponded to their dominant or non-dominant hand. They were given the cube-copying task twice, once via paper and once via tablet. The results between paper- and tablet-based tasks were more likely to be concordant in participants with a non-paretic dominant hand ( z = 2.80, p = 0.005) when the stroke type, education years, and sex were included in the model. All participants with discordant test results had a paretic dominant hand and showed lower muscle power in the wrist and hand muscles. In conclusion, cognitive function in patients with a paretic dominant hand may be underestimated in the cube-copying task, because it requires handwriting ability. This could be prevented by using a touch-screen device.